Incentive-compatible pollution control policies under asymmetric information on both risk preferences and technology - Peterson, Jeffrey M.; Boisvert, Richard N. (My University, 2013)
This article proposes a method to accommodate asymmetric information on farmers’ risk preferences in designing voluntary environmental policies. By incorporating stochastic efficiency rules in a mechanism design problem, the government can find incentive-compatible policies by knowing only the general class of risk preferences among farmers. The model also accounts for hidden information on technology types and input use. The method is applied empirically to simulate a pollution control program in New York. Results suggest that participation incentives would be inadequate for many risk-averse producers if the government does not account for the diversity in risk preferences.
Keywords: Asymmetric information; Mechanism design; Nonpoint pollution; Risk preferences